2016
DOI: 10.1007/s10548-016-0491-5
|View full text |Cite
|
Sign up to set email alerts
|

Brain Activation Patterns Characterizing Different Phases of Motor Action: Execution, Choice and Ideation

Abstract: Motor behaviour is controlled by a large set of interacting neural structures, subserving the different components involved in hierarchical motor processes. Few studies have investigated the neural substrate of higher-order motor ideation, i.e. the mental operation of conceiving a movement. The aim of this functional Magnetic Resonance Imaging (fMRI) study was to segregate the neural structures involved in motor ideation from those involved in movement choice and execution. An index finger movement paradigm wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…Evidence from both PD and FTD suggest that such deficits are associated with changes in the frontostriatal motor network. [97][98] We identified only four studies looking at the language profile of EOAD, 79,80,81,82 with mixed reports over the presence of language dysfunction. One study showed impaired comprehension for words, sentences, and commands, 81 while another described a patient who developed full aphasia.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from both PD and FTD suggest that such deficits are associated with changes in the frontostriatal motor network. [97][98] We identified only four studies looking at the language profile of EOAD, 79,80,81,82 with mixed reports over the presence of language dysfunction. One study showed impaired comprehension for words, sentences, and commands, 81 while another described a patient who developed full aphasia.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, such decrease in activation is associated with more careful behavioral adjustment in response to the social stimulus, presumably to minimize error (i.e., executing the opposite action). Specifically, premotor areas (BA 6) and anterior cingulate cortex have been shown to activate parametrically to the neural computations of goal-directed actions (Fincham, Carter, Van Veen, Stenger, & Anderson, 2002;Gardini et al, 2016), while superior temporal regions have been robustly involved in visuo-spatial processing supporting motor planning (Hanakawa, Dimyan, & Hallett, 2008;Shah-Basak, Chen, Caulfield, Medina, & Hamilton, 2018). Overall, this is consistent with the down-regulation of a spatial processing and motor planning neural network likely to track the mental set of the prepotent stimulus-response behavior.…”
Section: Prestimulus Neural Impact Of Cuementioning
confidence: 53%
“…Even small head motions may produce noise in brain scans (Power et al, 2012 ; Satterthwaite et al, 2012 ; Van Dijk et al, 2012 ), which proposed a challenge of integrate neuroimaging techniques into motor tasks. Researchers have designed a few tasks, which require a small range of motion such as finger tapping (Stoodley et al, 2012 ; Gardini et al, 2016 ), reaching and grasping (Culham et al, 2003 ), and lower limb joint motions (Kapreli et al, 2006 ). To expand knowledge on neural correlates of motor performance, feasible motor tasks should be developed to fit the setting of research employing the neuroimaging techniques.…”
Section: Discussionmentioning
confidence: 99%